Beyond antipsychotic efficacy and toward an individualized therapeutic strategy: analysis of the systemic, metabolic, and inflammatory effects of olanzapine, haloperidol, and their combination in schizophrenic patients - Alharbi, Nayef Samah; Hamdy, Noha Alaa; Aboubakr, Esam M.; Alharbi, Mansour; Ali, Mostafa A.; Alharbi, Ghaleb; ElMallah, Ahmed Ibrahim (Frontiers in Pharmacology, 2026)
IntroductionOlanzapine (OLZ), haloperidol (HALP), and their combination, are widely used antipsychotics; the majority of studies focuses on their therapeutic efficacy, leaving significant gaps in understanding their systemic impacts. Hence, the present study was conducted to investigate their systemic, metabolic, and inflammatory impact on schizophrenic patients.MethodsA total of 75 schizophrenic patients and 25 healthy volunteers were involved and monitored over a six-month period. Study groups were as follow; normal control, OLZ (20 mg/day), HALP (10 mg/day), and OLZ (20 mg/day) + HALP (5 mg/day). The parameters of metabolic, inflammatory, and neuronal transmitters, along with cardiovascular, hepatic, and renal functions were determined.ResultsIn this study we found that OLZ and HALP produced a noticeable decrease in potassium and chloride ions, while their combination decreased potassium, chloride and calcium. OLZ and OLZ + HALP significantly prolonged QTc, while OLZ and HALP individual administration increased SBP and CK-MP respectively. HbA1C levels not significantly affected by tested drugs, while OLZ produced a significant reduction in LDL and HDL levels, while OLZ + HALP modestly decreased LDL levels. renal assessment revealed a significant increase in both creatinine and urea concentrations in the OLZ + HALP group compared to other groups, whereas hepatic function showed no significant differences between the treated groups. OLZ significantly decreased total bilirubin and increased ALP activity, while HALP significantly reduced total and direct bilirubin levels. OLZ and OLZ + HALP produced a significant increase in body weight and waist circumference, which was not found in HALP-treated patients. Schizophrenic patients had reduced dopamine levels that was not significantly affect by OLZ or OLZ + HALP administration, while HALP administration normalized dopamine levels. Schizophrenic patients had significantly higher levels of serotonin compared to controls, that was normalized by our tested drugs. Ghrelin levels were significantly lower in schizophrenic patients, and it was significantly increased by HALP administration. Leptin hormone significantly elevated in schizophrenics, and was significantly decreased by HALP administration. Schizophrenic patients exhibited markedly elevated levels of IL-17, IL-6, and TNF-α, that dramatically decreased by tested drugs, and the combined regimen showed the highest impact.ConclusionThis study provides valuable insights into the systemic, metabolic, and inflammatory effects of tested drugs, support the individualized therapeutic approaches in schizophrenic patients to optimize clinical outcomes and minimizing long-term systemic risks.